The gender knot : unraveling our patriarchal legacy / Allan G. Johnson. - Johnson, Allan G. (Temple University Press, 2014)
'The Gender Knot', Allan Johnson's response to the pain and confusion that men and women experience by living with gender inequality, explains what patriarchy is (and isn't), how it works, and what gets in the way of understanding and doing something about it.